Functional assessment of geriatric patients in regard to health-related quality of life (HRQoL) - Muszalik M (Dove Medical Press, 2014)
Marta Muszalik,1 Tomasz Kornatowski,2 Halina Zielińska-Więczkowska ,3 Kornelia Kędziora-Kornatowska ,1 Ate Dijkstra41Clinic of Geriatrics, Nicolaus Copernicus University Collegium Medicum in Bydgoszcz, Bydgoszcz, Poland; 2Department of Preventive Medicine and Environmental Health, Nicolaus Copernicus University Collegium Medicum in Bydgoszcz, Bydgoszcz, Poland; 3Department of Pedagogy and Nursing Didactics, Nicolaus Copernicus University Collegium Medicum in Bydgoszcz, Bydgoszcz, Poland; 4Research group iHuman, NHL University for Applied Sciences, Leeuwarden, the NetherlandsPurpose: The main aim of our research was to evaluate general health, functioning, and performance parameters, as well as care problems of Geriatric Clinic inpatients in relation to deficits in fulfilling needs. The assessment of health-related quality of life was also performed.Patients and methods: The research subjects were patients attending the Clinic of Geriatrics: 149 women and 78 men; 227 persons in total. The research was carried out using a diagnostic poll method, with the application of the Activities of Daily Living questionnaire of assessment of daily efficiency on the basis of the Katz index, the Instrumental Activities of Daily Living questionnaire, the Care Dependency Scale used to measure the level of care dependency and human needs, and the Nottingham Health Profile scale.Results: The results showed that the majority of respondents achieved high and medium levels of functional capability. The main problems associated with the fulfillment of needs were difficulties with the adoption of appropriate body posture, movement restrictions, and problems related to participating in unassisted leisure activities outside the home. The general deficit in fulfilling the needs of the patients was low. The most significant problems were related to sleep disorders, restrictions in freedom of movement, loss of vital energy, and ailments resulting in the observable presence of pain.Conclusion: Good daily functioning of elderly patients significantly depended on their intellectual and mental efficiency. Elderly patients require a comprehensive, holistic approach to a variety of problems that occur with aging.Keywords: daily activity, elderly people, human needs